(3GdJSjjQ GdESJQGJjLj ddehGQO GdHTQjI aj JMSjf COGA GdeDSSIs - (3UHQjfI(B, (3JQZjfjs ((3YeGf(B:s (3OGQ GdGYUGQ GdYdej ddfTQ hGdJhRjY(B,s, 2016)
(3GdJSjjQ GdESJQGJjLj ddehGQO GdHTQjI,GdESJQGJjLjI,GdJSjjQ GdGSJQGJjLj,GdJSjjQ GdGSJQGJjLj ddehGQO GdHTQjI,OhQ GdJSjjQ GdESJQGJjLj ddehGQO GdHTQjI,JSjjQ GdeYQaI,JSjjQ GdegGQGJ,OhQ GdJSjjQ GdGSJQGJjLj ddehGQO GdHTQjI aj JMSjf COGA GdeDSSIs
Keywords: (3EOGQI GdCaQGO,EOGQI GdCYeGds